2008
DOI: 10.1107/s0108270108017150
|View full text |Cite
|
Sign up to set email alerts
|

Two new types of oxyfluorotellurates(IV): ScTeO3F and InTeO3F

Abstract: In the course of a general study of oxyfluorotellurates(IV), materials likely to exhibit interesting nonlinear optical properties, the crystal structures of the new phases scandium tellurium trioxide fluoride, ScTeO(3)F, and indium tellurium trioxide fluoride, InTeO(3)F, belonging to two different structural types and also differing from that of the recently published MTeO(3)F (M = Fe, Ga and Cr) series, have been determined. The ScTeO(3)F structure can be described as an intergrowth of two different layers of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…The comparison of the present glass and antiglass phases with the already known stable and nonhygroscopic oxyfluorotellurites (e.g., MTeO 3 F (M = Fe, Ga, Cr, In, and Sc)) strongly suggests that their high thermal stability should exclude the presence of short Te–F bonds as observed in all these oxyfluorotellurites. In fact, the Te cations are connected to 4 or 5 oxygen atoms at short and medium distances and also to 2 or 3 fluorine atoms at longer distances (2.5–3 Å), with these last anions also being part of the anionic polyhedra of Fe, Ga, Cr, In, and Sc at a shorter distance. It is therefore suggested that a similar situation occurs in the present glass and antiglass structures with polyhedra TeO 3–5 F 2–3 , F anions also all being connected to Zr cations by strong bonds, thus explaining the unexpectedly high resistance to moisture of these phases.…”
Section: Resultssupporting
confidence: 55%
“…The comparison of the present glass and antiglass phases with the already known stable and nonhygroscopic oxyfluorotellurites (e.g., MTeO 3 F (M = Fe, Ga, Cr, In, and Sc)) strongly suggests that their high thermal stability should exclude the presence of short Te–F bonds as observed in all these oxyfluorotellurites. In fact, the Te cations are connected to 4 or 5 oxygen atoms at short and medium distances and also to 2 or 3 fluorine atoms at longer distances (2.5–3 Å), with these last anions also being part of the anionic polyhedra of Fe, Ga, Cr, In, and Sc at a shorter distance. It is therefore suggested that a similar situation occurs in the present glass and antiglass structures with polyhedra TeO 3–5 F 2–3 , F anions also all being connected to Zr cations by strong bonds, thus explaining the unexpectedly high resistance to moisture of these phases.…”
Section: Resultssupporting
confidence: 55%
“…It is reported that combination of two different functional units to one compound is an effective method to create novel NCS and SHG materials. Additionally, different building blocks are suitable for producing brand new anion frameworks and enrich the structure chemistry of the inorganic compounds. We have been interested in assembling lone-pair electrons and tetrahedral groups together to make new NCS architectures and SHG materials for decades. The LPE groups were focused on selenite or tellurite containing Se­(IV) or Te­(IV) cations. We created the first boroselenite B 2 Se 2 O 7 , which is composed of SeO 3 triangle pyramids and BO 4 tetrahedra and crystallized in the chiral space group of P 2 1 2 1 2 1 .…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the limited vitreous domain of the TeO 2 –InF 3 system has been evidenced and some glass‐ceramics have been elaborated. It is noteworthy that only three crystalline compounds have been reported in the literature up to now in this system: InTeO 3 F, InTe 2 O 5 F and In 3 TeO 3 F 7 7–9 . Interestingly, we show the stabilization of a novel and unreported disordered crystalline phase, namely, an anti‐glass, in the 75TeO 2 –25InF 3 glass composition by controlling the thermal treatment of the parent glass.…”
Section: Introductionmentioning
confidence: 64%